Pengaruh Foreign Direct Investment, Inflasi, Nilai Tukar Dan Trade Openness Terhadap Pertumbuhan Ekonomi Negara D-8 - Zara Nurul Arifa; Nurjannah Nurjannah; Asnidar A (Benefit: Journal of Bussiness, Economics, and Finance, 2026)
This study aims to determine the effect of Foreign Direct Investment, Inflation, Exchange rates, and Trade Openness on economic growth in D-8 countries. The data used in this study are secondary data obtained from the world bank. This study employs panel data regression analysis for the periode 2020-2024, using the fixed effect model as the selected model. The results show that, partially, Foreign direct investment has a negative and insignificant effect on economic growth, inflation has a negative and significant effect on economic growth, the exchange rate has a positive and insignificant effect on economic growth, and trade openness has a positive and significant effect on economic growth. Simultaneously, Foreign direct investment, inflation, exchange rates, and Trade openness have a significant effect on economic growth in D-8 countries.